The politics of widowhood and re-marriage among the Luo of Kenya - Gunga, Samson O. (Philosophical Association of Kenya, 2009)
This study utilises philosophical deliberation to analyse the psycho-social and emotional conflicts that arise out of widowhood practices in the Luo community of Kenya. Towards this end, it explores the attendant effects of Luo widowhood practices on family, power and gender relations, and suggests resolutions to the challenges they generate